INDEPENDENSI AKUNTAN PUBLIK : SEBUAH REKAPITULASI - Agnes Maria; Djohan Pinnarwan (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2003)
So far, auditor’s independence has been the central theme of auditing- related discussions. Since the birth of auditing pmfessbn, these kinds of discussions has already existed. This paper attempts to recollect part of those discussions by reviewing die relevant literatures. This recollection is not the first attempt that has ever been done, but this paper is particularly unique in these respects, (1) it not only reviews the researches on auditor's independence, but also reviews the discussions about what is the meaning of “auditor’s independence’by different auditing-experts, (2) it includes die conceptual frameworks of the perceptions on auditor’s independence, and (3) it attempts to summarize the issues of “where we are now